Can community policing reduce perceived disorder? Results from a quasi-experiment in Trinidad and Tobago - Johnson, Devon (Policing and society, 2022)
This impact evaluation tests the effects of community policing, with an emphasis on problem-oriented policing, on perceived social and physical disorder in a disadvantaged Caribbean community. We use a pre-post, quasi-experimental design with two groups. The data include three waves of citizen surveys carried out in both groups. We use outcome measures developed from exploratory and confirmatory factor analysis and a difference-in-differences approach to compare changes in perceived social and physical disorder over time between residents in the treatment and comparison areas. Both the treatment and comparison areas experienced statistically significant small to modest reductions in perceived social and physical disorder between wave 1 (2006) and wave 2 (2007); the decrease was more pronounced in the treatment area. No significant changes in perceived social or physical disorder occurred between wave 2 (2007) and wave 3 (2008). Item-level analyses indicated that the composite measures of disorder masked important changes at the item level. The results suggest that community policing with a problem-solving approach can improve residents’ perceptions of social and physical disorder. The findings highlight the need to consider the nature of the community policing intervention and the quality and dosage of its implementation.